Taxi Driver’s Perception Towards Taxi Management in Kathmandu Valley: A Structural Equation Model Analysis - Ghimire, Anshu; Puri, Vaibhav; Devkota, Niranjan; Mahato, Surendra; Paudel, Udaya Raj (Journal of Innovation in Academia, 2023)
Taxi drivers around the world operate in a mobile environment that challenges the traditional concept of the workplace. They play a vital role in enabling us to reach our destinations with ease, security, and time-saving benefits. Therefore, transportation is considered one of the five crucial infrastructure facilities for the development of a country. The current study aims to analyze the factors that determine taxi drivers' perceptions of taxi management in Kathmandu Valley, Nepal. The results, obtained through Structural Equation Modeling (SEM), reveal five constructs fitting within the model. The findings conclude that accessibility, convenience, price, and intention to use taxi management are significantly related to each other. This indicates that all four variables significantly influence taxi drivers' perceptions of taxi management. As a result, this study suggests that the taxi industry must adapt to taxi management practices to enhance customer engagement.